Microfabrication technology for pancreatic cell encapsulation - Desai, Tejal A (Expert opinion on biological therapy, 2002)
The inadequacy of conventional insulin therapy for the treatment of Type I diabetes has stimulated research on several therapeutic alternatives, including insulin pumps and controlled-release systems for insulin. One of the most physiological alternatives to insulin injections is the transplantation of insulin-secreting cells. It is the beta-cells of the islets that secrete insulin in response to increasing blood glucose concentrations. Ideally, transplantation of such cells (allografts or xenografts) could restore normoglycaemia. However, as with most tissue or cellular transplants, the cellular grafts, particularly xenografts, are subject to immunorejection in the absence of chronic immunosuppression. Thus, it is of great interest to develop new technologies that may be used for insulin delivery or pancreatic cell transplantation. This review describes a new approach to cellular delivery based on micro- and nanotechnology. Utilising this approach, nanoporous biocapsules are bulk and surface micromachined to present uniform and well-controlled pore sizes as small as 7 nm, tailored surface chemistries and precise microarchitectures, in order to provide immunoisolating microenvironments for cells. Such a design may overcome some of the limitations associated with conventional encapsulation and delivery technologies, including chemical instabilities, material degradation or fracture and broad membrane pore sizes.